Profiling the metabolite changes of Klebsiella pneumoniae infected lung organ / Nurnazurah Faisal - Faisal, Nurnazurah (2015)
Metabolomics is the scientific study of the unique chemical fingerprint that a specific cellular processes leave behind. The focus of this study is to identify the metabolite changes between the control (noninfected) group and the Klebsiella pneumoniae infected group. The mixture of water: methanol: chloroform (1 :2:2) was used as the extraction solvent. After that, the extracted metabolites were analysed by LC/MS-QTOF and then further analysed by the MassHunter Qualitative Analysis and Mass Profiler Professional software for the significant metabolites associated with the Klebsiella pneumoniae infection. The numbers of extracted metabolites are 164 metabolites. After filtration by the Mass Profiler Professional, the number was decreased to 24 metabolites. Next, the metabolomics data were analysed by the web paged tool, MetP A for the significant metabolic pathways. Based on the MetP A analysis, the most expressed and significant pathways involved in the Klebsiella pneumoniae infection are retinol metabolism, arachidonic acid metabolism and D-glutamine and D-glutamate metabolism. These metabolic pathways involve directly and indirectly in activation of the immune system. Though, further study need to be conducted for further verification of specific biomarker(s) involved.